Barriers and Facilitators to Implementing Healthy Food Retail Programs: Extension Agents’ Perceptions - Kristin Riggsbee (Journal of Human Sciences and Extension, 2021)
The purpose of this cross-sectional study was to understand the perceptions Extension professionals have about healthy food retail programs (HFRPs). Family and Consumer Science (FCS) agents from one state in the southeastern United States were interviewed about their definitions of HFRPs, what challenges and benefits existed, and strategies for successful HFRP implementation. Participants reported that HFRPs would bring immense benefits to their communities, including expanding the recognition of Extension. However, one specific suggestion that was identified was hands-on training needed before initiating HFRPs, particularly on strategies for relationship development with retail store owners.